Amniocentesis in twin pregnancies - Siraprapa Supadilokluck (2018)
Objective: To describe the experiences in diagnostic amniocentesis in twin pregnancies. Methods: The computerized database and medical records of pregnant women attending Maternal Fetal Medicine Unit of the hospital for diagnostic amniocentesis at 16-20 weeks gestation between January 1992 and December 2006 were retrospectively reviewed. Results: During 15 years of experience, 7,890 amniocenteses at 16-20 weeks gestation were performed for prenatal diagnosis, including 174 procedures in 87 twin pregnancies. The mean gestational age at the time of amniocentesis was 17.13 ± 3.35 weeks. Preterm birth rate defined as the delivery before 36 gestational weeks was 36.24%. The total fetal loss rate was 5.17%, however, the procedure related fetal loss within 2 weeks after the procedure was 1.15%. Conclusion: Based on our limited data and previous studies, we can counsel patients undergoing twin amniocentesis at mid-trimester that the fetal loss rate may be slightly higher than that of singleton amniocentesis. © 2008 Springer-Verlag.